IMP3 Immunohistochemical Expression in Inverted Papilloma and Inverted Papilloma-Associated Sinonasal Squamous Cell Carcinoma. (17th February 2021) - Hakim, Sarah A.; Abd Raboh, Nermine M.; Shash, Lobna S.
Abstract : Sinonasal inverted papilloma (IP) has a propensity for malignant transformation. Although the IP-associated squamous cell carcinoma (SCC) is rare, it has a poor prognosis. To the best of our knowledge, this is the first study to assess IMP3 immunohistochemical (IHC) expression in sinonasal tumors and to compare it to the Ki-67 IHC expression and to other established clinicopathological parameters. A retrospective study was conducted on three groups which consisted of 72 cases of sinonasal IP, 20 age-matched samples of normal respiratory epithelium, and 15 cases of sinonasal SCC associated with IP, which were obtained from the archives of the Pathology Lab of Ain Shams University Specialized and Ain Shams University Hospitals during the period from January 2012 to December 2019. An IHC study was performed to evaluate IMP3 and Ki-67 expression in the three groups, with correlation of IMP3 expression to established clinicopathological parameters of sinonasal SCC on top of IP. Both IMP3 and Ki-67 showed a sharp rise in expression in the sinonasal SCC group. In addition, there were statistically significant differences in expression values between the 3 groups (P = 0.001 ). Receiver Operating Characteristic (ROC) analysis revealed that IMP3 and Ki-67 could be used to discriminate sinonasal SCC from control and IP lesions, with sensitivity and specificity of 100% and 81.5% for IMP3, respectively, and 100% and 62.5% for Ki-67, respectively. Spearman's rho revealed that both IMP3 and Ki-67 were significantly related to the lymph node and tumor stages but not to the tumor grade. ROC analysis was performed to select cut-off scores for progression and survival for IMP3, and accordingly, Kaplan-Meier analysis showed correlation between IMP3 and overall survival, local recurrence-free survival, and metastasis-free survival in sinonasal SCC cases at the selected cut-off values. Based on our results, IMP3 could serve as a promising diagnostic, prognostic, and therapeutic marker for IP-associated sinonasal SCC.